Tuning Ruthenium Carbene Complexes for Selective P−H Activation through Metal‐Ligand Cooperation. Issue 69 (11th November 2021) - Feichtner, Kai‐Stephan; Scharf, Lennart T.; Scherpf, Thorsten; Mallick, Bert; Boysen, Nils; Gessner, Viktoria H.
Abstract: The use of iminophosphoryl‐tethered ruthenium carbene complexes to activate secondary phosphine P−H bonds is reported. Complexes of type [( p‐ cymene)‐RuC(SO2 Ph)(PPh2 NR)] (with R = SiMe3 or 4‐C6 H4 −NO2 ) were found to exhibit different reactivities depending on the electronics of the applied phosphine and the substituent at the iminophosphoryl moiety. Hence, the electron‐rich silyl‐substituted complex undergoes cyclometallation or shift of the imine moiety after cooperative activation of the P−H bond across the M=C linkage, depending on the electronics of the applied phosphine. Deuteration experiments and computational studies proved that cyclometallation is initiated by the activation process at the M=C bond and triggered by the high electron density at the metal in the phosphido intermediates. Consistently, replacement of the trimethylsilyl (TMS) group by the electron‐withdrawing 4‐nitrophenyl substituent allowed the selective cooperative P−H activation to form stable activation products. Abstract : Metal ligand cooperation. Two different iminophosphoryl‐substituted methandiide‐derived carbene complexes have been applied in the P−H bond activation of secondary phosphines. Surprisingly versatile reaction outcomes were observed depending on the imine substituent at the methandiide ligand and the phosphine used. While more‐electron‐rich combinations led to either cyclometallation or an imine transfer, electron‐poor combinations enabled selective P−H bond activation, thus impressively demonstrating the importance of tuning the M=C in this type of carbene complex for bond activation.